2021
DOI: 10.1016/j.hpb.2020.11.081
|View full text |Cite
|
Sign up to set email alerts
|

Early versus Late Recurrence of Hepatocellular Carcinoma after Surgical Resection Based on Post-recurrence Survival: An International Multi-institutional Analysis

Abstract: Background To define early versus late recurrence based on post-recurrence survival (PRS) among patients undergoing curative resection for hepatocellular carcinoma (HCC). Methods Patients who underwent curative-intent resection for HCC between 2000 and 2017 were identified from an international multi-institutional database. The optimal cut-off time point to discriminate early versus late recurrence was determined relative to PRS. Results Among 1004 patients, 443 (44.1%) patients experienced recurrence with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In fact, while recurrence following transplantation for HCC has been reported to be as low as 10-14%, recurrence after liver resection for early-stage HCC can be as high as 50-70%. [2][3][4][5][6] Liver transplantation is not, however, available to many patients due to limited services at certain medical centers, poor access to liver donors, and prolonged wait times. 19,20 In fact, a subset of patients with early-stage HCC and underlying chronic liver disease who are on the waiting list are at risk of tumor progression and drop out from the list.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, while recurrence following transplantation for HCC has been reported to be as low as 10-14%, recurrence after liver resection for early-stage HCC can be as high as 50-70%. [2][3][4][5][6] Liver transplantation is not, however, available to many patients due to limited services at certain medical centers, poor access to liver donors, and prolonged wait times. 19,20 In fact, a subset of patients with early-stage HCC and underlying chronic liver disease who are on the waiting list are at risk of tumor progression and drop out from the list.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of recurrence in the remnant liver can be as high as 50-70% among patients with concomitant chronic liver disease. 5,6 Salvage liver transplantation may be feasible for patients with transplantable recurrence (TR) after initial tumor resection with better long-term outcomes than re-resection or ablation. [7][8][9] Salvage transplantation is not feasible in all clinical situations, as some patients develop non-transplantable recurrence (NTR) despite strict surveillance after resection.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the recurrence patterns and survival outcomes of patients with LR are different from those of patients with ER. Compared with patients with ER, patients with LR often present with multiple lesions but have better survival outcomes (25,26). Therefore, identifying reliable and accurate markers for the early detection of LR of HCC is critical.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel HCC risk score, the age-male-ALBIplatelets (aMAP) score, was developed and validated in a global, multi-ethnic, multi-etiological, prospective cohort study of chronic hepatitis to accurately predict the risk of hepatitis-related HCC (29). Age and gender were shown to be related to HCC recurrence while platelet count, serum albumin and serum bilirubin levels were co-related with liver function in multiple studies (17,25,30,31). Therefore, this scoring system accurately stratifies the risk of HCC development for patients with hepatitis and can improve early HCC detection by developing personalized monitoring strategies.…”
Section: Introductionmentioning
confidence: 99%